2017
DOI: 10.18203/2320-6012.ijrms20170655
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in oral carcinoma and the relationship between tumor thickness and regional nodal involvement: a pilot study in a semi urban population in New Delhi, India

Abstract: Background: Oral squamous cell carcinoma (OSCC) is a major public health problem worldwide, with approximately 275,000 cases annually and a strong association with risk factors like smoking. It is a subtype of head & neck cancer involving the oral cavity.  The present study evaluated the role of various risk factors in the development of oral carcinoma among our patient population.Methods: A total of 40 cases of oral carcinoma with radical neck dissection were evaluated. Data on the age, personal history a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…This may be due to male subjects are use more tobacco, alcohol, betel nut, betel leaf than female. Almost similar to the findings observed by the various investigators from different countries 16,23,24 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This may be due to male subjects are use more tobacco, alcohol, betel nut, betel leaf than female. Almost similar to the findings observed by the various investigators from different countries 16,23,24 .…”
Section: Discussionsupporting
confidence: 90%
“…So betel leaf is the major risk factor in present series. Gupta and Mehta (2000), Balaram et al (2002) and Jetley et al (2017) found similar results in their studies 23,25,26 . Jetley et al (2017) observed the favored smoking method was bidi and cigarette 23 .…”
Section: Discussionsupporting
confidence: 67%